EXPLAINING PURCHASE INTENTIONS AND ONLINE SHOPPING BEHAVIOUR AMONG YOUNG MALAYSIAN MUSLIM CONSUMERS - Wan Nawang, Wan Rasyidah; Muhamed Shukri, Muhammad Huzairil Syaqir (I-iECONS e-proceedings, 2023)
The commercialisation of the Internet in 1991 ushered in the era of e-commerce, in which online shopping plays an increasingly important role. Despite this, Malaysian online shopping has grown slowly, with the COVID-19 pandemic being the catalyst. Since then, Malaysians have become increasingly reliant on the internet and the proliferation of smarter, more powerful devices to shop for goods and services. As online shopping becomes more popular and has become the norm, the question arises as to what factors influence Malaysians' online shopping intentions and behaviour. The objective of the proposed study is to investigate the online shopping intentions and behaviour of young Muslim consumers in Malaysia. By using the Theory of Reasoned Action (TRA) as the underlying theory, this study will extend the variables to include new variables such as trustworthiness, security and safety, loyalty, and marketing information that influence online shopping intentions. In addition, consumer intentions that influence behaviour will also be investigated. This study is expected to contribute to theory while highlighting practical implications for academics and practitioners in the fields of marketing, consumer behaviour, and online shopping.